(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Filipinos are popularly known as food lovers; this is probably the reason why many delectable Filipino dishes had risen. Filipinos love eating rice. Given that Filipinos have different foods to offer, the researchers decided to create a business that offers purely Filipino dishes from different regions of the country. Rice toppings or rice bowl is the fastest and easiest way to eat on the go. The researchers chose the rice toppings business to represent different foods in the country in a convenient way. The researchers distributed survey questionnaires to 50randomly selected respondents aged18 years old and above. The respondents included employees, students, and residents near the area, as well as passersby in Kiko Camarin, Caloocan City. The researchers proposed that their business will be a hit in the market. The business proposed different kinds of Filipino foods from famous local places as customers approved through the survey conducted. Quantitative research was used here to collect and analyze the data obtained from different respondents. The results of this study showed that the products are budget-friendly and convenient to eat. The results of this feasibility study showed how the respondents understood the proposed business. The researchers are confident that the product is convenient and delicious at the same time. It can attract local consumers to buy the product. The business is feasible and viable in the market. The researcher’s marketing strategy is simple but will attract a wide range of customers. The financial stability is acquired based on the projected and budget to ensure the effectiveness of the product.